Second Year Winner: The Jig: WRIT 2710, Grammar and Proofreading. CD: Dunja Baus, TA: Megan Hillman. - Pries, Madelaine (Jan Rehner Prize for Writing, 2017)
This assignment challenged students to think about language and writing by constructing a sentence of 200 words using a variety of tools. "The Jig" treats readers to a compelling piece of writing that is rich and full of energy. This piece highlights the writer’s ability to incorporate technical elements and difficult vocabulary into an interesting story. The writer has managed to tell a lively and engaging story under very specific and constrained requirements. Ultimately, "The Jig" goes well beyond the requirements of the assignment and leaves the reader wanting to know what else will happen next time the girl in the story sits at the piano.